Management research in East and West - Amdam, Rolv Petter; Lang, Rainhart, 1953- (Baltic journal of management ;, 2007)
Management research has a long tradition rooted in the early 20th century of the Western hemisphere, but as Hofstede has put it, "in a global perspective, US management theories contain several idiosyncrasies not necessarily shared elsewhere." The rise of Japanese management and "postmodern" organizations in China and Korea has led to more diversity in management practice and research. Moreover, with the fall of the iron curtain, new developments in the management of the "East European capitalism" may also contribute to other and alternative approaches in management research. This e-book of th